Prevalence and Associated Risk Factors of Pregnancy Induced Hypertension Among Pregnant Women at Burao General Hospital, 2024 - Ahmed, Sadam Ismail; Awed, Abdiwahab Ahmed; Guled, Abdirizak Ahmed (RADINKA JAYA UTAMA PUBLISHER, 2025)
This research, conducted as a cross-sectional study at Burao General Hospital in 2024, aimed to determine the prevalence and associated risk factors of pregnancy-induced hypertension (PIH). The study, which utilized a sample of 77 randomly selected pregnant women, found that a significant portion of participants, 27.3%, had been diagnosed with PIH, while the majority (72.7%) had normal blood pressure. The analysis, performed using SPSS version 21, identified several key risk factors strongly associated with PIH. The study found a statistically significant link between PIH and whether a woman had received antenatal care (ANC) follow-up before data collection, a personal history of chronic hypertension, and a family history of chronic hypertension. The p-values for these associations were 0.040, 0.000, and 0.001, respectively, indicating a high degree of statistical significance. These findings highlight a concerning prevalence of PIH in the study population and underscore the importance of targeted interventions. To improve maternal and fetal outcomes, the researchers recommend increasing initiatives for both pregnant women and healthcare providers regarding the risks and early signs of PIH. Additionally, they stress the need for regular ANC visits and lifestyle modifications to manage risk. For women identified as high-risk, the study recommends developing specific intervention strategies, such as tailored treatment plans, frequent monitoring, and specialized support services. These measures are crucial to mitigating the risks associated with PIH and improving overall maternal health.